Reducing teachers’ workload or deskilling ‘core’ work? Analysis of a policy response to teacher workload demands - Stacey, Meghan; Gavin, Mihajla; Fitzgerald, Scott; McGrath-Champ, Susan; Wilson, Rachel (Taylor & Francis, 2023)
Teacher workload is a growing problem internationally. In this article, we analyse an attempt by the state education bureaucracy of New South Wales (NSW), Australia, to address this through the ‘Quality Time Program’. Drawing on labour process theory and Carol Bacchi’s framework of ‘What’s the problem represented to be?’, we analyse how the Quality Time policy documents conceptualise and aim to address a particular kind of teacher ‘workload problem’. We argue the policy defines the ‘problem’ as one of efficiency. At the same time, through use of the category of ‘administration’ the policy proposes the reduction of ‘core’ work, such as lesson planning, representing a potential deskilling of teachers. We argue that policies such as the Quality Time Program reflect the way in which teachers’ work is emerging as a site of contestation in the context of workload reduction efforts, requiring ongoing monitoring and analysis.